Climate-resilient infrastructure : adaptive design and risk management - Ayyub, Bilal M. (American Society of Civil Engineers, 2018)
"MOP 140 provides guidance for developing or enhancing of methods for infrastructure analysis and design to achieve infrastructure resilience targets while minimizing life-cycle costs in a changing climate"-- Provided by publisher
Keywords: City planning -- Climatic factors.; Building, Stormproof.; Infrastructure (Economics); Sustainable urban development.; Environmental protection.; Environmental impact analysis.; elektronické knihy; electronic books